2011
DOI: 10.1111/j.1540-5893.2011.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Racial Bias of the White Male Capital Juror: Jury Composition and the “Empathic Divide”

Abstract: This article examines the nature of racial bias in the death sentencing process. After reviewing the various general explanations for the continued significance of race in capital cases, we report the results of an empirical study in which some aspects of racially biased death sentencing are examined in depth. Specifically, in a simulated capital penalty-phase trial setting where participants were assigned to small group ''juries'' and given an opportunity to deliberate, white male jurors were significantly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 71 publications
4
72
1
Order By: Relevance
“…The disproportionate removal of African Americans, coupled with the heightened chance of women being excluded, also increases the likelihood that the capital jury will be disproportionately populated by white men, who are especially likely to survive the death qualification process. This, too, raises the risk of unequal treatment in the capital context, since white male jurors have been found to be particularly susceptible to racial bias against African American capital defendants (Lynch and Haney ; Bowers, Steiner, and Sandys ). Thus, death qualification has the potential to set a pernicious process in motion, disproportionately excluding African Americans from the pool of available venirepersons while simultaneously increasing the representation of white men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disproportionate removal of African Americans, coupled with the heightened chance of women being excluded, also increases the likelihood that the capital jury will be disproportionately populated by white men, who are especially likely to survive the death qualification process. This, too, raises the risk of unequal treatment in the capital context, since white male jurors have been found to be particularly susceptible to racial bias against African American capital defendants (Lynch and Haney ; Bowers, Steiner, and Sandys ). Thus, death qualification has the potential to set a pernicious process in motion, disproportionately excluding African Americans from the pool of available venirepersons while simultaneously increasing the representation of white men.…”
Section: Discussionmentioning
confidence: 99%
“…We examine the various ways in which death qualification might create a potential jury pool that is heavily biased in favor of capital punishment, particularly through the disproportionate removal of African Americans from the jury pool due to their opposition to the death penalty. Finally, extending our own prior research on juror demographics and capital decision making (Lynch and Haney ), we examine potential differences between the way that whites and African Americans assess the nature and importance of various aggravating and mitigating factors—the factors that capital jurors are instructed to consider and weigh as they decide between a sentence of life or death. Thus, we explore whether and in what ways African American respondents may be more receptive to mitigating evidence, such that their disproportionate removal would tend to produce a strongly death‐leaning jury pool.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research has also identified a variety of factors that can influence jury decisions such as race (Lynch & Haney, 2011), perceived similarity (Mitchell & Byrne, 1973), attractiveness (Weiten & Diamond, 1979) and pretrial publicity (DaftaryKapur et al, 2014). What research has yet to examine is the effect of stereotypes about Greek life organizations on jury decisions.…”
Section: Stereotypes About Greek Letter Organizationsmentioning
confidence: 99%
“…Because we are more likely to empathize with people who are more like ourselves, black defendants who have heavily white male juries are at a distinct disadvantage [33]. Using a group of jury-eligible, nonstudent participants, visual materials rather than the less externally valid trial transcripts, a realistic courtroom setting, and a jury deliberation component Lynch and Haney [34,35] investigated this white male bias by examining the ways in which the white male jurors differed from others; namely women and nonwhite participants. Participants were assigned to one of four conditions created by manipulating the race of the defendant (black vs. white) and the race of the victim (black vs. white) in a capital trial.…”
Section: What Should the Penalty Be?mentioning
confidence: 99%